Sintesis Suara Bernyanyi Dengan Teknologi Text-To-Speech untuk Notasi Musik Angka dan Lirik Lagu Berbahasa Indonesia - Jonathan Jonathan; Yohanes Suyanto (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Singing is a work of art that can not be separated from human life. It then makes a research about develop the art of singing by technology will brings a useful impact for such a wide aspect of human life. This research is trying to synthesize singing voice with TTS (text-to-speech) technology, as it capability to produce sound with certain pronunciation at certain frequency of sound. Inputs that used in the system are texts of song in TXT format that contain the information of numbered musical notation and lyrics in Indonesian. These inputs will converted to a phonetic transcription, for then synthesize of song voice can done based on the transcription. In general, the system made successfully synthesize song voices with some feature that based on the convention of numbered musical notation. Based on 30 people of respondents, the song voice synthesized has 81.71% of accuracy with 6.24% of deviation standard. The syntax of song text also reputed as a user-friendly convention with only up to 3 times re-compilation done to synthesize 8 bar of song text by each of respondents without any error.